Diagnostic Accuracy of The TrueNat MTB/RIF Assay And Comparison With The Reference Standards To Detect Pulmonary Tuberculosis And Rifampicin Resistance in Sputum Samples From Patients Attending A Tertiary Care Hospital in Bhubaneswar, India - Barik, Braja Sundar; Das, Shritam; Singh, Khusbu; Chandan, Sudatta; Kumar Swain, Subrat; Nayak, Prasanti; Mishra, Omkar Abadesh; Hussain, Tahziba; Das, Dasarathi; Pati, Sanghamitra (National Journal of Community Medicine, 2024)
Background: A rapid and accurate diagnostic tool is necessary for correct diagnosis and treatment of TB. This study evaluated and compared the sensitivity, specificity and concordance of TrueNAT MTB/RIF assay with smear microscopy, Xpert MTB/RIF and MGIT culture. Methods: In all, 4500 patients (1500 each of patients with Diabetes, elderly and HIV-positive patients) attending the Chest and TB department of Capital Hospital, Bhubaneswar were screened. 392 sputum samples were collected from presumptive TB patients. Standard diagnostic procedures (Smear Microscopy, Xpert MTB/RIF, TrueNAT MTB tests and MGIT culture) were performed. Results: This diagnostic efficiency of rapid molecular TrueNAT MTB/RIF assays have similar properties as Xpert MTB/RIF and may be used for the diagnosis of TB and Rifampicin resistance. Among participants, the TrueNAT MTB shows the sensitivity of 80%, 100% and 78.26% while the specificity was 97.9%, 95.83% and 100%. The concordance rates between all tests were calculated and the TrueNAT MTB showed good agreement with the culture method among study participants (κ = 0.793, 0.554, and 0.862, respectively). Conclusion: The TrueNAT assays are sensitive for diagnosis of TB patients with faster turnabout time from testing to treatment and economical.